A pediatric case of Gordonia otitidis bacteremia detected by long-term blood culture. Issue 10 (October 2022) - Kobayashi, Takao; Otake, Shogo; Mori, Takeshi; Hasegawa, Daiichiro; Kosaka, Yoshiyuki; Ohkusu, Kiyofumi; Kasai, Masashi
Abstract: For immunocompromised patients receiving chemotherapy or bone mallow transplantation, slow-growing bacteria should also be considered one of the pathogenic microorganisms. However, there is no evidence pertaining to the microbiological tests associated with a patient with febrile neutropenia before peripheral blood stem cell harvest (PBSCH). We report a case of a 4-year-old cancer-bearing female presenting with a catheter-related bloodstream infection due to Gordonia otitidis . We detected G. otitidis from long-term blood cultures for approximately 6 days and prevented iatrogenic bacteremia by identifying the same organism from the culture of the PBSC sample and postponing the scheduled PBSCH. If febrile neutropenia occurs before PBSCH, we should collect multiple sets of blood cultures and culture them for a longer period.